2021
DOI: 10.3389/fphar.2021.774808
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Comorbidities in Patients With Psoriasis: Focusing on Risk, Biological Therapy, and Pathogenesis

Abstract: Psoriasis is a chronic inflammatory disease characterized by erythematous scaly plaques, accompanied by systemic damage that leads to the development of multiple comorbidities. In particular, the association between psoriasis and cardiometabolic comorbidities, including cardiovascular diseases (CVDs), obesity, diabetes mellitus, and metabolic syndrome, has been verified in a considerable number of clinical trials. Moreover, the increased risk of cardiometabolic comorbidities positively correlates with psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 150 publications
(185 reference statements)
0
16
0
Order By: Relevance
“…Taking into account the link between systemic inflammation and CV diseases, it is conceivable that controlling inflammation by systemic agents may positively impact the CV risk in PsD ( 73 , 74 ). It is now well demonstrated that conventional synthetic agents such as methotrexate (MTX), but also TNFi, improve the CV burden of patients with RA ( 75 ).…”
Section: Clinical Implications Of Cardiometabolic Conditions In Psdmentioning
confidence: 99%
“…Taking into account the link between systemic inflammation and CV diseases, it is conceivable that controlling inflammation by systemic agents may positively impact the CV risk in PsD ( 73 , 74 ). It is now well demonstrated that conventional synthetic agents such as methotrexate (MTX), but also TNFi, improve the CV burden of patients with RA ( 75 ).…”
Section: Clinical Implications Of Cardiometabolic Conditions In Psdmentioning
confidence: 99%
“…Based on our findings, we believe that the preliminary assessment of comorbidities with routine dermatological investigations in psoriatic patients is essential to prevent possible cardiovascular mortalities. The recommended guidelines for the screening of cardiovascular comorbidities in psoriatic patients is provided by the National Psoriasis Foundation and the American Heart Association [32] (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the evidence of the psoriasis-CVD crosstalk, several efforts have been made to understand whether a systemic treatment of psoriasis may lead to the control of the systemic inflammation associated with the skin manifestations, and to limit the risk of CV events ( 55 , 76 78 ). The 2021 Group for Research and Assessment of Psoriasis and Psoriatic arthritis (GRAPPA) treatment recommendations for psoriasis are summarized in ( 79 ).…”
Section: Targeting Key Inflammatory Pathways To Reduce CV Risk In Pso...mentioning
confidence: 99%